Peran Perwakilan Diplomatik Indonesia dalam Melindungi Kepentingan Nasional pada Situasi Eskalasi Geopolitik: Studi Kasus Hubungan Indonesia–Iran - Shindy Dwianisa; Syafariah Nata Putri; Yuli Anggraini; Laura Shafa Qurratun Nisa (CV. ITTC INDONESIA, 2026)
This study aims to analyze the role and effectiveness of Indonesian diplomatic representatives in Iran in protecting national interests in situations of geopolitical escalation, particularly regarding access to energy routes through the Strait of Hormuz. The method used is normative legal research with a legislative and conceptual approach, and using primary, secondary, and tertiary legal materials. The results of the study indicate that Indonesian diplomatic representatives carry out the functions of representation, negotiation, protection, and strategic reporting in accordance with the 1961 Vienna Convention. However, their effectiveness faces various obstacles such as limited bargaining power, geopolitical complexity, policy uncertainty, limited diplomatic instruments, and national energy dependence. Thus, diplomatic relations do not automatically guarantee the protection of national interests, because they are greatly influenced by the dynamics of each country's interests in the global geopolitical context.